PENGARUH pH LARUTAN PENGEKSTRAK TERHADAP RENDEMEN DAN KARAKTERISTIK PEKTIN ALBEDO KULIT BUAH DURIAN - Yusuf, Alexander Nathanael; Putra, Nengah Kencana; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i01.p08, 2020)
The purposes of this research is to determine the effect of pH solution during extraction of pectin from the albedo of durian rind on its characteristic and yield resulted from the extraction which resulted with the highest amount of yield and best pectin characteristic. This research is using Randomized Block Design (RBD) with the treatment of the pH solution during the extraction with the pH being used is (2.0; 2.5; 3.0; 3.5 and 4.0),. The treatment is repeated three times so that were obtained 15 unit of experiment and data were analyzed by variance analysis. If any effect showed by the treatment then the analysis were followed by the Duncan test. The test result indicate that the pH of the solution have an effect to the yield and characteristic of pectin extracted from the albedo of durian rind. The treatment that produce pectin with the best characteristic and the most yield are obtained at solution with pH 2.0 with the result of yield (4.07%), equivalent weight (767.39 mg) level of  metoksil (10.06%), ash content (4.67%). And levels of anhidrogalacturonat acid (84.04%) Keywords : pH , pectin, fruit peel durian, albedo